RIA fractions contain mesenchymal stroma cells with high osteogenic potency. (December 2015) - Kuehlfluck, Pamela; Moghaddam, Arash; Helbig, Lars; Child, Christopher; Wildemann, Britt; Schmidmaier, Gerhard; ,
Abstract: Introduction: The gold standard for treatment of non-union is the transplantation of autologous bone from iliac crest. As an alternative, material can be harvested by femoral reaming with the Reamer-Irrigator-Aspirator ® (RIA)–System. This material might be a source for human mesenchymal stroma cells (MSCs) with osteogenic potency. The aim of this study was the characterisation of cells harvested with the RIA system and the comparison of their properties with cells isolated from bone marrow ("BM") and fat tissue ("adipose"). The RIA material was separated into the liquid aspiration fraction ("liquid") and the solid RIA fraction. From the solid RIA fraction the cells were cultured either directly ("native") or after collagenase digestion and filtration ("filtrate"). Stem cell characteristics were analysed and the osteogenic potential was investigated in vitro and in vivo . Materials & Methods: Fat tissue and bone marrow were harvested from nine patients (three women, six males, with a mean of 48.1 years) with atrophic non-union RIA material. The cells were isolated and characterised by flow cytometry, three lineage differentiation capacities and colony-forming unit fibroblast assay. Gene expression profiles were performed and osteogenic differentiation in vivo was analysed. Results: All three RIA fractions contained mesenchymal stromal cells (MSCs) as demonstrated by CFU-F assay, three linage differentiation and surface marker analysis. The RIA-MSCs exhibited a significantly higher osteogenic potential in vitro compared to adipose-MSCs, whereas no difference was seen compared to BM-MSCs. Quantitative RT-PCR analysis revealed an expression of osteogenic markers in all isolated cells. The implantation of MSCs with β-TCP scaffolds into the mice muscle showed significantly higher bone formation for the filtrate RIA-MSC, native RIA-MSC and BM-MSC groups compared to the adipose-MSC group. The filtrate RIA-MSCs formed twice as much new bone in vivo compared to BM-MSCs. Conclusion: The present study showed high potency of cells isolated by reaming. Even in the irrigation fluid, which is normally discarded, cells with the characteristics of stromal stem cells were isolated. In comparison to adipose-MSCs and BM-MSCs, the RIA-MSCs showed a similar or even better osteogenic potential in vitro and in vivo and this supports their usability in orthopaedic surgery.